ANALISIS KONSEKUENSI HUKUM DARI PERKAWINAN SIRI TERHADAP PEREMPUAN DAN ANAK - Angel Victoria; Mia Hadiati (Jurnal Hukum Adigama, 2022)
Siri marriage is considered as an illegal relationship by the state, so that the child born from the marriage is considered legal and varies according to religion. This position is based on Article 43(1) of the Marriage Law which states that a child born out of wedlock can only have civil relations with his mother and family. Based on the decision of the Constitutional Court, she can have a civil relationship with a man out of wedlock, her biological father. , said: National relations are between children born out of wedlock and their mothers and their families, and between fathers and their children in so far as a natural relationship between them can be scientifically explained; it can support technical evidence and/or other evidence such as relationships, including civil contacts with family members. In this case, unregistered marriages are considered to only provide protection and freedom to the men. Amendments to Article 43 (1) of the UUP generally apply to provide full legal protection to all born children and oblige fathers to take full responsibility for their children in accordance with the law.